Let J ( n ) = x → 0 lim ( ( ln ( 1 + x ) ) n 1 − ( x − 2 x 2 + 3 x 3 − ⋯ + n ( − 1 ) n + 1 x n ) n 1 )
Also A = n = 1 ∑ ∞ n 2 J ( n ) And R = n = 1 ∑ ∞ n ! J ( n )
Now let R + A = K ln H − S N
Where K , H , N are positive integers, H is a prime number, while S is a non negative real number
Find N + K + S + H
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
For presentation purposes, initial manipulation steps have been omitted
Calculation of A :
A = − j = 1 ∑ ∞ j ( j + 1 ) ( − 1 ) j = − j = 1 ∑ ∞ ∫ 0 1 j ( − 1 ) j x j d x = − ∫ 0 1 j = 1 ∑ ∞ j ( − 1 ) j x j d x = ∫ 0 1 ln ( 1 + x ) d x = 2 ln 2 − 1
Calculation of R : R = j = 0 ∑ ∞ j ! ( − 1 ) j ⋅ ( j + 2 ) 1 = j = 0 ∑ ∞ ∫ 0 1 j ! ( − 1 ) j x j + 1 = ∫ 0 1 j = 0 ∑ ∞ j ! ( − 1 ) j x j + 1 d x = ∫ 0 1 e − x x d x = 1 − e 2
Let p n ( x ) = 2 − x + 3 x 2 − 4 − x 3 + . . . + n ( − 1 ) n + 1 x n − 1 , such that, ( x ( p n ( x ) ) ) n 1 = R H S .
J ( n ) = lim x → 0 ( ( x p n ( x ) + n + 1 ( − 1 ) n + 2 x n + 1 + x n + 2 q n ( x ) ) n 1 − ( x ( p n ( x ) ) ) n 1 ) , where q n ( x ) is a polynomial. J ( n ) = lim x → 0 x n − x n + 1 P n ( x ) + n x n − 1 n + 1 ( − 1 ) n + 2 x n + 1 − x 2 n + 1 Q n ( x ) 1 − x n − x n + 1 P n ( x ) 1 , for appropriate polynomials P n ( x ) , Q n ( x ) . J ( n ) = lim x → 0 x n 1 ( ( 1 + ( x P n ( x ) − n n + 1 ( − 1 ) n + 2 x n + x n + 1 Q n ( x ) ) + ( x P n ( x ) + . . . ) 2 + . . . ) − ( 1 + ( x P n ( x ) ) + ( x P n ( x ) ) 2 + . . . ) ) . inside the brackets, everything of order x n and below cancels, except − n n + 1 ( − 1 ) n + 2 x n .
Hence, J ( n ) = n n + 1 ( − 1 ) n + 1 .
A = ∑ n = 1 ∞ n ( n + 1 ) ( − 1 ) n + 1 = lim x → − 1 ∑ n = 1 ∞ n ( n + 1 ) x n = lim x → − 1 ∫ ∫ ( ∑ n = 0 ∞ x n ) d x 2 = lim x → − 1 ∫ ∫ 1 − x 1 d x 2 = lim x → − 1 ∫ − lo g ( 1 − x ) d x So, A = lim x → − 1 x − ( x − 1 ) lo g ( 1 − x ) = − 1 + 2 lo g ( 2 ) .
R = ∑ n = 1 ∞ ( n + 1 ) ! ( − 1 ) n + 1 n = lim x → − 1 ∑ n = 1 ∞ ( n + 1 ) ! x n + 1 n = lim x → − 1 ∑ n = 1 ∞ x 2 ( ( n + 1 ) ! n x n − 1 = lim x → − 1 x 2 ( d x d x e x − x 1 ) .
So R = lim x → − 1 x 2 ( x e x − x 2 e x + x 2 1 ) = lim x → − 1 x e x − e x + 1 = 1 − e 2 .
Hence, A + R = 2 lo g ( 2 ) − e 2 .
Problem Loading...
Note Loading...
Set Loading...
Let f = ln ( 1 + x ) and let f n be the sum of the first n terms of the maclaurin expansion of f . Do note that when I use f ( n ) , it means the nth derivative of f , and when I use f n , it means the nth exponent of f . The question requires for J ( n ) = x → 0 lim f n 1 − f n n 1 = x → 0 lim j ( n , x ) .
j ( n , x ) = f n 1 − f n n 1 = f n f n n f n n − f n = ( f n − f ) ( j = 0 ∑ n − 1 f n j − n f − 1 − j ) = − ( ( n + 1 ) ! f ( n + 1 ) ( a ) x n + 1 ) ( j = 1 ∑ n ln ( 1 + x ) j f n n + 1 − j 1 )
Where a is some real, 0 ≤ a ≤ x . I used f − f n = ( n + 1 ) ! f ( n + 1 ) ( a ) x n + 1 that follows from Taylor's Theorem , the Lagrange form of the remainder .
Hence
x → 0 lim j ( n , x ) = x → 0 lim − ( n + 1 ) ! f ( n + 1 ) ( a ) x n + 1 ( j = 1 ∑ n ln ( 1 + x ) j f n n + 1 − j 1 ) = − ( n + 1 ) ! f ( n + 1 ) ( 0 ) x → 0 lim j = 1 ∑ n ln ( 1 + x ) j f n n + 1 − j x n + 1 = − ( n + 1 ) ! f ( n + 1 ) ( 0 ) x → 0 lim j = 1 ∑ n ln ( 1 + x ) n + 1 x n + 1 = − ( n + 1 ) ! n f ( n + 1 ) ( 0 ) x → 0 lim ln ( 1 + x ) n + 1 x n + 1 = − ( n + 1 ) ! n f ( n + 1 ) ( 0 ) 1 n + 1 = ( − 1 ) n + 1 ⋅ n + 1 n
First line to second I used 0 ≤ a ≤ x . From second to third I used how f n behaves asymptotically the same as ln ( 1 + x ) when x is close to 0 . Fourth to fifth I used L'Hopital .
Now the main problem has been solved. The rest follows suit. (See comments for details)